Troglomorphic adaptations on the northern European frontier: the phylogeny of the cave Pseudosinella (Hexapoda, Collembola) in the Western Carpathians - Kováč, Ĺubomír; Žurovcová, Martina; Raschmanová, Natália; Jureková, Nikola; Papáč, Vladimír; Parimuchová, Andrea (Frontiers in Ecology and Evolution, 2023)
Introduction Using an integrative taxonomic approach, we investigated the morphological and molecular characters to identify the species of the genus Pseudosinella occurring in caves of the Western Carpathians and to clarify their phylogenetic relationships. Based on morphological characters, we hypothesized that Pseudosinella aggtelekiensis (Stach, 1929) and Pseudosinella paclti (Rusek, 1961) originated from different phyletic lineages. Methods We used the barcoding fragment of the mtDNA COI gene from 87 individuals from 16 caves to reconstruct the phylogenetic history of the genus Pseudosinella. Results The molecular phylogenetic tree revealed two distinct species groups with allopatric distributions. The first group consisted of P. aggtelekiensis populations from the Slovak Karst and three undescribed species from fragmented and isolated karst areas in southeastern Slovakia. The second group, P. paclti populations in the Central Western Carpathians, was merged. This group included Pseudosinellamuranensis, a new species taxonomically described in this work. It is characterized by highly developed troglomorphic features and is restricted to a small karst area, the Muranska planina Plateau. The phylogeny of the genus Pseudosinella from the caves of the Western Carpathians revealed a Miocene diversification. According to molecular calibration, the two distinct Pseudosinella lineages were separated in the Middle Miocene, about 14.51 Mya, followed by further diversification in the P. paclti lineage 10.89 Mya and in the P. aggtelekiensis lineage 11.14 Mya. Discussion This phylogeny is consistent with the uplift of Triassic limestones during the early formation of the Western Carpathians in the Paratethys region and the initial development of caves during this period. The study provides further important evidence that the Western Carpathians played a significant role as an independent speciation center of the obligate cave fauna in Europe.